'The pleasures of traveling in Liberty Plains': Practical Piety and Childhood Education Through Material Culture in the American Quaker Community. Issue 1 (1st June 2022) - Lindman, Janet Moore
Abstract : Quaker spirituality encompassed a range of activities, from prayer, meditation and worship to reading, writing and conversation. It also included interaction with what scholars call 'material religion'. Analysis of an allegorical map entitled 'A Map of the Various Paths of Life', created by American minister George Dillwyn in 1794, provides a window into the relationship between Friends' religious practice and material culture. It enables us to examine the use of objects to inculcate Quaker values and provide a 'guarded education' to Quaker youth. A multidisciplinary approach will be utilised to analyse the map and its importance to practical piety among American Friends in the eighteenth and nineteenth centuries.